2012
DOI: 10.1027/0269-8803/a000065
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Early Perceptual Processing by Emotional Expression and Acquired Valence of Faces

Abstract: Modulation of early perceptual processing by emotional expression and the affective valence of faces was explored in an event-related potential (ERP) study. An associative procedure was used where different neutral faces changed to happy, to angry or, in a control condition, stayed the same. Based on these changes in expression, participants had then to identify each neutral face as belonging to a friendly, hostile, or neutral individual. ERP measures revealed modulations at occipital-temporal sites of the P10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 64 publications
10
48
1
2
Order By: Relevance
“…We have reported in a previous paper results that show that the associative learning procedure used in the present study is also effective to modulate early perceptual processing of individual faces as shown by event-related potentials (Aguado et al, 2012). Taken together, what these results suggest is that positive and negative emotional expressions have power enough to modify the affective value of human faces and that this change is manifest at both central (brain responses) and peripheral levels (facial reactions).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We have reported in a previous paper results that show that the associative learning procedure used in the present study is also effective to modulate early perceptual processing of individual faces as shown by event-related potentials (Aguado et al, 2012). Taken together, what these results suggest is that positive and negative emotional expressions have power enough to modify the affective value of human faces and that this change is manifest at both central (brain responses) and peripheral levels (facial reactions).…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, there is evidence suggesting that explicit instructions to evaluate an affective stimulus may dampen spontaneous, automatic affective responses (e.g., Lieberman, 2011) of which the EMG responses here studied are an example. In fact, a previous study by Aguado et al (2012) using a paradigm similar to that employed in the present experiment showed a different pattern of modulation of brain potentials to S1 neutral faces followed by emotional S2 faces and to those same S1 faces presented alone. Finally, S1 duration during the categorization trials was different for each participant and trial, as presentation of the stimulus was terminated by the categorization response.…”
Section: Emg Resultsmentioning
confidence: 87%
“…On the other hand, multiple fast cortical pathways forming part of a feedforward and feedback mechanism consistute an equally plausible mechanism for rapid expression perception (Liu & Ioannides, 2010;Pessoa & Adolphs, 2010). (Aguado et al, 2012;Eger, Jedynak, Iwaki, & Skrandies, 2003;Schupp et al, 2004). On the other hand, modulations of the N170 faceresponsive component (120-200 ms) are consistently reported (see Hinojosa, Mercado, & Carreti e e, 2015 for a meta-analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Una serie de estudios han encontrado que de forma paralela el reconocimiento de la expresión emocional del rostro puede modular el componente N170 tanto en amplitud como en latencia. Aguado et al (2012), compararon rostros con expresiones emocionales de ira y felicidad contra rostros neutros y encontraron mayor amplitud ante rostros de ira comparados con los rostros de felicidad y neutros. Baggott, Palermo y Fox (2011), detectaron mayor amplitud de rostros que expresaban miedo, ira y tristeza comparados con los rostros neutros.…”
Section: Discussionunclassified